Influence of Nitrogen Content on the Corrosion Behavior of Powder Metallurgy Nickel-Free Austenitic Stainless Steel - Weili Yu; Changhai Du; Hongren Shen; Hao He; Yong Yu; Yimin Li; Fenghua Luo (Advances in Materials Science and Engineering)
Herein, powder metallurgy gas-solid nitriding was used to prepare a high-nitrogen Ni-free austenitic stainless steel with more than 1.0 wt.% N. Study of the microstructures and corrosion resistances of the as-prepared samples revealed that the corrosion weight loss, size, number of corrosion pits, and corrosion depth decreased as the N content increased from 1.19 to 1.37 wt.%. The self-corrosion current densities of the alloys were determined from their potentiodynamic polarization curves. The changes in the capacitive arc radius as demonstrated by the Nyquist curves were consistent with the conclusions of the immersion corrosion analysis; that is, a high N content leads to a high corrosion resistance.